Coronary artery calcium: associations with brain magnetic resonance imaging abnormalities and cognitive status. - Rosano, Caterina; Naydeck, Barbara; Kuller, Lewis H; Longstreth, William T; Newman, Anne B (J Am Geriatr Soc, 2005)
OBJECTIVES: To evaluate the association between coronary atherosclerosis and subclinical brain magnetic resonance imaging (MRI) abnormalities and between coronary atherosclerosis and abnormal cognitive function (dementia/mild cognitive impairment). DESIGN: Cross-sectional. SETTING: The Cardiovascular Health Study (CHS), an epidemiological study of risk factors for cardiovascular disease in older adults. PARTICIPANTS: Four hundred nine men and women, mean age 79, recruited from the Pittsburgh center of the CHS. MEASUREMENTS: Coronary atherosclerosis was defined according to the level of coronary artery calcification (CAC), as measured using electronic beam tomography. Subclinical brain MRI abnormalities included ventricular enlargement, white matter hyperintensities, and number of subcortical brain infarcts. Brain MRI and CAC measurements were performed between 1998 and 2000 at the Pittsburgh center of the CHS. Prevalence of brain MRI abnormalities and abnormal cognitive status were examined across quartiles of the CAC score, before and after controlling for age. Multivariate logistic regression models were used to assess whether CAC level was associated with abnormalities of brain MRI or abnormal cognitive status. RESULTS: Older adults with high CAC scores were more likely to have more-severe brain MRI abnormalities, including subcortical infarction and high white matter hyperintensities. The associations between CAC and ventricular enlargement showed a similar but not significant trend. The presence of any of the MRI abnormalities attenuated the association between CAC and abnormal cognitive status. CONCLUSION: Older adults with higher levels of CAC were more likely to have more-severe brain MRI abnormalities and abnormal cognitive status.
Keywords: Aged; Brain; Calcinosis; Cognition Disorders; Coronary Artery Disease; Cross-Sectional Studies; Dementia; Female; Humans; Logistic Models; Magnetic Resonance Imaging; Male; Risk Factors; United States